The Effect of Return on Assets, Return on Equity, and Net Profit Margin on the Share Price of PT Bank Central Asia Tbk during 2019–2023 - Sariyati Sariyati; Guyub Nuryanto; Alya Girdayani (Lentera Ilmu Nusantara, 2026)
This study aims to examine the effects of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) on the share price of PT Bank Central Asia Tbk during the 2019–2023 period. The study employed a quantitative approach using secondary data obtained from the official websites of the Indonesia Stock Exchange and PT Bank Central Asia Tbk. A total of 20 observations were analyzed using multiple linear regression. The analysis included classical assumption tests consisting of normality, multicollinearity, heteroscedasticity, and autocorrelation tests, followed by partial t-tests, a simultaneous F-test, and the coefficient of determination. The results indicate that ROA has a significant negative effect on the company’s share price, whereas ROE and NPM have significant positive effects. Simultaneously, ROA, ROE, and NPM have a significant effect on the share price of PT Bank Central Asia Tbk. The adjusted R-squared value of 0.907 indicates that the three financial ratios explain 90.7% of the variation in share price, while the remaining 9.3% is explained by other variables not included in this study. These findings demonstrate that profitability ratios play an important role in explaining changes in the company’s share price.